Transport infrastructures and sustainability of urban development - Kamp, Hendrik van der (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2002)
There is an increasing degree of concern over the continuing sprawl of low density development outwards from the Dublin Region and the leapfrogging pattern of commuter based housing development as urban centres some distance away from Dublin experience rapid development patterns in response to increases in metropolitan house prices. Interestingly, one contributing factor to this development pattern has been quoted as road infrastructure (Williams & Shiels, 1998). The construction of the M50 Cring motorway and improvement of all of the national primary road corridors connecting to it, have contributed to a wider catchment area for commuteTh . ln a way, the housing market in the region fonns a reasonably accurate and transparent illustration of the traditional trade--off theory of land prices (Alonso, 1965) where house buyers base their locational choice on the trade-off between lower house prices with higher travel to work costs.
Keywords: Urban geography -- Ireland